Factors Affecting Seaweed (Eucheuma cottoni) Production in Banten Province (Case in Lontar Village) - Handayani, Evi; Daris, Edmon; Ichdayati, Lilis Imamah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Seaweed is one of the plants that has a lot of potential as a functional food ingredient, active ingredient of drug preparation and even cosmetics that are quite natural in producing various pharmacological activities both as a source of antioxidants, antibacterials, antimicrobials and anticancer. Seaweed is currently a potential asset for areas that are able to produce it to meet the increasing market needs. Lontar Village, located in Banten Province, is one of the main seed producing areas. However, seed production factors are one of the main indicators that need to be used as a standard in this study, such as the length of the rope span, age characteristics, education characteristics, characteristics of the seed farmer's business experience. This type of research is quantitative and data is obtained primarily and secondarily. The data obtained were analyzed using the SPSS 26 program. The results of the study showed that the factors that influence seaweed production in Banten Province, especially Lontar Village, are influenced by the length of the rope span, age characteristics, education characteristics, characteristics of the seaweed farmer's business experience. The conclusion is that seaweed production is influenced by various characteristics, namely age, education, and seaweed farming experience.